Electroacupuncture for slow flow/no-reflow phenomenon in patients with acute myocardial infarction undergoing percutaneous coronary intervention: protocol for a pilot randomized controlled trial - Peng, Yanbin; Wei, Xuqiang; Wu, Feng; Fan, Min; Wang, Ke; Zhou, Jia (Frontiers in Cardiovascular Medicine, 2024)
Background Slow flow/no-reflow (SF-NR) during percutaneous coronary intervention (PCI) is associated with poor prognosis of patients with acute myocardial infarction (AMI). Currently, effective treatment is not available for SF-NR. Electroacupuncture (EA) has shown significant efficacy as an adjuvant therapy for many cardiovascular diseases by improving microcirculation and reducing ischemia-reperfusion injury. However, its effects on SF-NR in the AMI patients during PCI are not clear. This pilot trial aims to determine the efficacy of intraoperative EA in alleviating SF-NR in AMI patients undergoing PCI. Methods This prospective, single-center, randomized controlled, pilot trial will recruit 60 AMI patients scheduled for PCI at the Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, China. The patients will be randomized in a 1:1 ratio into the EA or the control groups. Patients in the control group will undergo standard PCI. Patients in the EA group will undergo intraoperative electroacupuncture while undergoing standard PCI. Incidence of SF-NR is the primary outcome for this study. This study will also assess secondary outcomes including cardiac biomarkers, inflammatory biomarkers, pain and anxiety scores, electrocardiography parameters, traditional Chinese medicine (TCM) symptom score, and major adverse cardiovascular and cerebrovascular events (MACCE). All the included patients will undergo laboratory tests including routine blood tests, levels of electrolytes, as well as liver and renal function tests. Patients will be followed up for 1 month after the procedure. Discussion This pilot trial will provide evidence for the potential benefits of intraoperative EA in improving microvascular perfusion and preventing or alleviating SF-NR during PCI in patients with AMI. If proven effective, intraoperative EA will provide a new and effective strategy against SF-NR and provide evidence for subsequent multicenter trials. Clinical Trial Registration ClinicalTrials.gov, identifier (ChiCTR2300072265). Registered on 8 June 2023.